Development of E-LKPD through a Problem-Based Learning Approach for Improving Student Learning Motivation at SMK Negeri 1 Pogalan Trenggalek - Basuki, Andi; Ramadhan, Rizky Arya (Journal of Economics Education and Entrepreneurship, 2023)
Technological developments in the modern era make educators required to develop interactive and innovative learning media. This study aims to produce an E-LKPD product with a Problem-Based Learning (PBL) approach in Public Relations & Protocol Subjects, to determine the feasibility of the product and to determine the difference in the average learning motivation of students in the class before and after using the E-LKPD product. The method used in this study is the modified Borg and Gall model. The results of the validation by experts and small group user trials showed that the E-LKPD with the PBL approach that was developed was declared to be very valid and effective for use in learning. The results of the percentage calculation show that there are differences in learning motivation before and after using the E-LKPD product, where students after using the product experienced a significant increase in learning motivation compared to those before using the E-LKPD product